Math, asked by monjyotiboro, 4 months ago

Can anyone solve 48 number?​

Attachments:

Answers

Answered by amansharma264
6

EXPLANATION.

⇒ A = {x ∈ R : x² + 6x - 7 < 0}. - - - - - (1).

⇒ B = {x ∈ R : x² + 9x + 14 > 0}. - - - - - (2).

As we know that,

From equation (1), we get.

⇒ A = {x ∈ R : x² + 6x - 7 < 0}. - - - - - (1).

⇒ x² + 6x - 7 < 0.

Factorizes the equation into middle term splits, we get.

⇒ x² + 7x - x - 7 < 0.

⇒ x(x + 7) - 1(x + 7) < 0.

⇒ (x - 1)(x + 7) < 0.

Put this point on wavy curve method, we get.

⇒ x ∈ (-7,1). - - - - - (a).

From equation (2), we get.

⇒ B = {x ∈ R : x² + 9x + 14 > 0}. - - - - - (2).

⇒ x² + 9x + 14 > 0.

Factorizes the equation into middle term splits, we get.

⇒ x² + 7x + 2x + 14 > 0.

⇒ x(x + 7) + 2(x + 7) > 0.

⇒ (x + 2)(x + 7) > 0.

Put this point on wavy curve method, we get.

⇒ x ∈ (-∞,-7) ∪ (-2,∞). - - - - - (b).

(1) = A ∩ B.

⇒ x ∈ (-7,1) ∩ (-∞,-7) ∪ (-2,∞).

Put this point on number line, we get.

⇒ x ∈ (-2,1).

(2) = (A \ B).

⇒ (A \ B) = (A - B) = {x ∈ R : -7 < x < -2}.

⇒ (A \ B) = (-7,-2).

Option [C] is correct answer.

                                                                                                                             

MORE INFORMATION.

Number of elements in different sets.

If A,B & C are finite sets and U be the finite universal set, then.

(1) = n(A ∪ B) = n(A) + n(B) - n(A ∩ B).

(2) = n(A ∪ B) = n(A) + n(B) [if A & B are disjoint sets].

(3) = n(A - B) = n(A) - n(A ∩ B).

(4) = n(A Δ B) = n[(A - B) ∪ (B - A)] = n(A) + n(B) - 2n(A ∩ B).

(5) = n(A ∪ B ∪ C) = n(A) + n(B) + n(C) - n(A ∩ B) - n(B ∩ C) - n(A ∩ C) + n(A ∩ B ∩ C).

(6) = n(A' ∪ B') = n(A ∩ B)' = n(U) - n(A ∩ B).

(7) = n(A' ∩ B') = n(A ∪ B)' = n(U) - n(A ∪ B).

Similar questions
Math, 4 months ago